Earnings Management by Indian Initial Public Offering Firms - Suri, Sneha (2016)
The present study examines the issue of earnings management by Initial Public offering firms (IPO) for a sample of Indian IPO firms listed from 2010 to 2013. IPO market is characterised by information asymmetry and IPO firms have incentive and opportunity to report inflated performance in years surrounding IPO. We hypothesize that the IPO firms report inflated financial performance and manage earnings with discretionary accruals in the pre-IPO years and the IPO year. In the post-IPO years, the reported performance and discretionary accruals decline. Results are consistent with our hypotheses and there is clear evidence of earnings management by Indian IPO firms. This scenario is detrimental to the interest of retail uninformed investors. The regulators and accountant standard setting bodies need to consider changes in disclosure requirements for Indian IPO firms.